Features of the development of the global gold market ("Journal "U". Economy. Management. Finance.", 2019)
The article reveals the essence and features of gold, both a precious metal and the main asset of the gold market. The data on the largest gold reserves in the gold and foreign exchange reserves of countries are given. The functions of the gold market are considered. The dynamics of gold prices for the period 2004-2018 is analyzed. The ratio of demand for gold and its supply for the first quarter of 2019 is given.
Keywords: world gold market; gold reserve; gold price dynamics; demand; sentence